(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Professionalism is a global quality expected in medical students’ along with clinical skills. Behavioral sciences have been included in 3rd year MBBS curriculum since 2014 at FJMU. The purpose of this change is to enhance Professionalism formally in addition to other areas of the subject. This study aims to determine effectiveness of studying behavioral sciences as a subject in enhancing elements of Professionalism. Subjects and Methods: The mixed-methods study was used and a sample of 240 3rd year medical students was taken by convenient sampling. In the first (quantitative) phase of the study, Penn State College of Medicine Professionalism Questionnaire (PSCOM-PQ) was administered before and after studying behavioral sciences as a subject, to collect pre and post statistical results about students’ attitudes towards professionalism. The results were analyzed by paired sample t-test. In the second (qualitative) phase, Focus Group Discussion (FGD) was conducted to reveal the reasons for professionalism development and role of Behavioral Sciences in its development. 8 students were selected by purposeful homogeneous sampling technique. FGD session was audio-taped and transcribed, finally thematic analysis was done. Results: The results showed highly significant increase (p-value= 0.00, t= -74.39, mean= -72, SD= 14.99) in the scores of Professionalism after studying behavioral sciences as a subject. The broad themes identified by FGD were “Professionalism Related Skills Learned through Behavioral Sciences” and “Modes of Information Transfers’ Role in Professionalism Understanding”. The professional skills conceptualized by the students included emotional stability, empathy, psychoeducation, confidentiality, competency and sense of responsibility. The participants felt that professionalism develops by the means of lectures, workshops, role plays, modeling and formal assessment sessions. Conclusion: Study of behavioral science has significant effect in the development of professionalism among MBBS students and is well received by third year MBBS students.